Cratonaia novaolindensis gen. et sp. nov. (Unionida, Silesunionoidea) from the Aptian of Brazil (Araripe Basin), and its implications for the early evolution of freshwater mussels - da Silva, Victor R. [UNESP]; Varejão, Filipe G. [UNESP]; Matos, Suzana A. [UNESP]; Fürsich, Franz T.; Skawina, Aleksandra; Schneider, Simon; Warren, Lucas V. [UNESP]; Assine, Mario L. [UNESP]; Simões, Marcello G. [UNESP] (Elsevier, 2020)
The fossil-rich carbonate deposits of the Aptian Crato Formation, Araripe Basin (Brazil) are one of the main Cretaceous Konservat-Lagerstätten of Gondwana, and have come to fame globally. However, information on fossils from deposits other than the famous laminites of the basal part of the unit is scarce. Herein, we describe the first bivalves of the suborder Silesunionidina Skawina and Dzik, 2011 in the order Unionida Gray, 1854 from South America. The specimens were collected from a 0.3–1-m-thick grey to yellow mudstone interval located 0.3 m above the laminated limestones of the lower part of the Crato Formation at Nova Olinda, State of Ceará. They comprise exquisite composite, internal and external moulds, preserving key anatomical characters. Based on the analysis of muscle scars, hinge and ornamentation, these bivalves are here assigned to a new genus and species, Cratonaia novaolindensis gen. et sp. nov. The presence of a series of small pedal elevator scars linearly arranged on the external wall of the umbonal cavity indicates that this is a member of the suborder Silesunionidina. The new form is the by far youngest representative of this group. Closely related bivalves were previously reported from Triassic deposits of Australia, Africa, Europe and potentially India. Detailed stratigraphic, sedimentological and taphonomic observations indicate that the new taxon thrived in a freshwater lake. The occurrence of Silesunionoidea in the Lower Cretaceous of South America indicates that the condition of the musculature in Mesozoic freshwater mussels needs to be established to assign them confidently at family level.
Keywords: Crato Formation; Palaeobiogeography; South America; Systematics; Taphonomy; Taxonomy